2009
DOI: 10.1038/mt.2008.294
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided, Lobe-specific Hydrodynamic Gene Delivery to Swine Liver

Abstract: Image-guided, lobe-specific hydrodynamic gene delivery to liver was assessed in pigs. The procedure involved image-guided insertion of a balloon catheter to the hepatic vein of the selected lobe from the jugular vein and hydrodynamic injection of plasmid DNA using a newly developed computer-controlled injection device. We demonstrated that the impact of the procedure was regional with minimal effects on neighboring lobes. Level of gene expression resulted from the procedure was 107 RLU/mg in the targeted lobes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 17 publications
6
119
0
Order By: Relevance
“…To avoid this adverse effect, we have described a retrograde cathetermediated gene delivery procedure 5 with the aim of locally reproducing the intrahepatic conditions mediated by tail vein hydrodynamic injection. However, all the studies reported in pigs 4,5,[11][12][13][14] and in human clinical trials 3 indicate that the efficiency of the procedure remains several orders of magnitude lower than observed in mice. The exact reason for the low gene transfer efficiency of retrograde injection is still unknown, but the low resistance of the sinusoid bed must be a very important factor, as DNA can easily travel across the liver segment after hepatic vein injection, reaching the portal vein and then freely returning to the inferior cava vein through another liver segment.…”
Section: Discussionmentioning
confidence: 98%
“…To avoid this adverse effect, we have described a retrograde cathetermediated gene delivery procedure 5 with the aim of locally reproducing the intrahepatic conditions mediated by tail vein hydrodynamic injection. However, all the studies reported in pigs 4,5,[11][12][13][14] and in human clinical trials 3 indicate that the efficiency of the procedure remains several orders of magnitude lower than observed in mice. The exact reason for the low gene transfer efficiency of retrograde injection is still unknown, but the low resistance of the sinusoid bed must be a very important factor, as DNA can easily travel across the liver segment after hepatic vein injection, reaching the portal vein and then freely returning to the inferior cava vein through another liver segment.…”
Section: Discussionmentioning
confidence: 98%
“…In gene therapy studies, hydrodynamic delivery of plasmid DNA has generated gene product at the therapeutic level and resulted in complete cure of diseases (8)(9)(10)(11). By combining the technique of image-guided catheter insertion with a computer-controlled injection device (12), we have demonstrated successful gene delivery to cells in the liver (13) and skeletal muscle (14) in pigs, suggesting that site-specific gene delivery can be achieved in large animals and it is feasible to apply hydrodynamic gene delivery to treatment of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The technique involves the rapid injection of large volumes of DNA solution into a peripheral (usually the tail) vein, using volumes amounting to B10% of the body weight in mice (B2.5 ml) 1,2 and B8-10% of body weight in rats (B20-25 ml). 3,4 However, although there have been six published reports in the pig [5][6][7][8][9][10] and one clinical trial, 11 none of these has provided levels of gene delivery remotely close to those seen in mice and rats. In the pig studies, levels of reporter gene expression were o1% of those in concurrent studies in rodents, while there was no substantive evidence for gene expression in the clinical study.…”
Section: Introductionmentioning
confidence: 99%